Implementation of Al-Islam Kemuhammadiyahan As Efforts to Improve Student Characteristics - Adi Syahputra; Mesiono Mesiono; Haidir Haidir (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2023)
The purpose of this research is to reveal how to plan, implement, and evaluate the results of Al-Islam Kemuhammadiyahan values as an effort to improve student character. This research is qualitative research with a descriptive approach. Sources of data came from students, principals, teachers and guardians of students at SMP Muhammadiyah 57 Medan, while school staff at SMP Muhammadiyah 57 Medan were additional data sources in this study. The results of the study revealed that: Planning and implementation of Al-Islam Kemuhammadiyahan learning as an effort to improve student character has been carried out according to the rules and made at the beginning of the semester before learning begins, in planning Al-Islam Kemuhammadiyahan learning plans adjusted to the provisions of the curriculum and student needs by selecting methods and media as well as paying attention to competency standards, core competencies, madrasah vision and mission, and student needs.